2023
DOI: 10.1128/jvi.00286-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Monoclonal Antibodies with Neutralizing Activity against Diverse SARS-CoV-2 Variants

Abstract: Omicron variants of SARS-CoV-2 acquired escape ability from host immunity and authorized antibody therapeutics and thereby have been spreading worldwide. We reported that patients infected with an early SARS-CoV-2 variant, D614G, and who received subsequent two-dose mRNA vaccination have high neutralizing antibody titer against Omicron lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…We observed that MO11 did not bind to the spike RBD of all of the variants tested ( Fig. 3B ), in contrast to the RBD-binding antibody MO7 isolated in our earlier work ( 7 ), indicating that the recognition site of MO11 is outside of the RBD.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…We observed that MO11 did not bind to the spike RBD of all of the variants tested ( Fig. 3B ), in contrast to the RBD-binding antibody MO7 isolated in our earlier work ( 7 ), indicating that the recognition site of MO11 is outside of the RBD.…”
Section: Resultssupporting
confidence: 82%
“…A human monoclonal antibody, MO11, was isolated from B cells of a convalescent COVID-19 patient who had been infected by SARS-CoV-2 D614G assumed from the onset period (July 2020) and then received three doses of an mRNA vaccination (Table S1) via the procedure described in our earlier study ( 7 ). The neutralizing activity of MO11 against SARS-CoV-2 variants was quantitatively evaluated by a plaque reduction assay using the authentic virus of major SARS-CoV-2 variants: a variant harboring spike D614G mutation (hereafter, D614G), Delta, Omicron BA.1, BA.2, BA.2.75, BA.5, BQ.1.1, XBB.1, XBB.1.5, XBB.1.16, and EG.5.1.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…However, cell-free systems are not suitable for the expression of more complicated protein formats such as scFvs (single chain fragment variables) and Fabs (fragment antigen binding). While there has been studies reporting the successful expression of scFvs and Fabs in cell-free systems 27,28,29,30,31 , our first hand experience indicates that cell-free systems are not reliable for the expression of these protein formats.…”
Section: Case Studiesmentioning
confidence: 88%